Pentingnya Alkitab Sebagai Sumber Pembelajaran Pendidikan Agama Kristen dalam Pembentukan Karakter Bagi Siswa Kelas 8 SMP di Sekolah Kasih Bapa Singkawang - Kristin Elsi; Simatauw, Marfy (Sekolah Tinggi Teologi Borneo, 2024)
Abstract: The Bible has an important role, namely being the basis of learning for Christianreligious education teachers. Every education undertaken by student teachers must have afuture goal for student development, including the formation of good character for eachstudent's personality.This research aims to describe the importance of the Bible as a learning source for Christianreligious education in forming students' character. The focus of this research is understandinghow important the Bible is as a basis for learning Christian religious education to improvestudent character formation. This research was conducted at the Kasih Bapa SingkawangSchool. And as data sources are teachers and students. In this research, the researcher used aqualitative approach, because this research intended to understand the phenomena experiencedby the research subjects. The data collection methods used by the researcher were interviewsand documentation.From the results of the data analysis, it was concluded that the importance of the Bible as asource of learning for Christian religious education in character building for grade 8 studentsof Junior High School (SMP) at the Kasih Bapa Singkawang School has been implemented,but because the students' background is not from Christian circles, it is a little difficult toimplement it. To achieve the goal of forming the character of junior high school students,coaching activities should be increased with the aim of forming student character so that studentcharacter is not yet fully formed.Keywords: Importance of the Bible, CharacterAbstrak: Alkitab memiliki peranan penting yaitu menjadi dasar pembelajaran bagi gurupendidikan Agama Kristen, setiap pendidikan yang ditempuh oleh siswa guru pasti nyamemiliki tujuan kedepannya bagi perkembangan siswa termasuk pembentukan tertanam nyakarakter yang baik untuk pribadi setiap siswa.Penelitian ini bertujuan untuk mendeskripsikan pentingnya Alkitab sebagai sumberpembelajaran pendidikan Agama Kristen dalam pembentukan karakter siswa. Fokus penelitianini yaitu memahami bagaimana penting nya Alkitab sebagai dasar pembelajaran pendidikanAgama Kristen untuk meningkatkan pembentukan karakter siswa, penelitian ini dilakukandisekolah Kasih Bapa Singkawang. Dan sebagai sumber data adalah guru dan siswa. Dalampenelitian ini peneliti menggunakan pendekatan kualitatif, karena penelitian ini bermaksuduntuk memahami fenomena tentang apa yang dialami oleh subjek penelitian, Metodepengumpulan data yang digunakan peneliti adalah wawancara dan dokumentasi.Dari hasil analisis data diperoleh kesimpulan Pentingnya Alkitab sebagai sumberpembelajaran pendidikan Agama Kristen dalam pembentukan karakter bagi siswa kelas 8Sekolah Menengah Pertama (SMP) di Sekolah Kasih Bapa Singkawang, sudah dilakukan namun karena latar belakang siswa bukan dari kalangan Kristen maka sedikit kesulitan untuk penerapan dilakukan untuk mencapai tujuan dalam pembentukan Karakter siswa Sekolah Menengah Pertama, jadi hendaknya kegiatan pembinaan ditingkatkan dengan tujuan untuk membentuk karakter siswa sehingga karakter siswa belum terbentuk sepenuhnya.Kata kunci: Pentingnya Alkitab, Karakter